2008
DOI: 10.1016/j.jneuroim.2008.05.016
|View full text |Cite
|
Sign up to set email alerts
|

CCL genes in multiple sclerosis and systemic lupus erythematosus

Abstract: This follow up study aims to refine the roles of previously suggested candidate genes (CC chemokine ligands or CCLs) in multiple sclerosis (MS), and to test these markers in another autoimmune disorder, systemic lupus erythematosus (SLE). After stringent correction for multiple testing, we reject the importance of previously suggested borderline associations with CCLs in MS. A new finding is the differential distribution of CCL8 marker alleles and a haplotype in extreme severity subgroups of MS. In SLE, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Normal controls: Buccal swab specimens of 466 Caucasian healthy controls were obtained from staff members, spouses of MS patients and constructors working at the MSRCNY, New York. Specimens from these patients and controls were included in a parallel study [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Normal controls: Buccal swab specimens of 466 Caucasian healthy controls were obtained from staff members, spouses of MS patients and constructors working at the MSRCNY, New York. Specimens from these patients and controls were included in a parallel study [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Although a direct relationship between the genetic polymorphisms of CC chemokine genes and risk of NHL have never been reported, genetic variations in these genes have been associated with risk of HIV-1 infection and autoimmune disorders (36), which are established risk factors for NHL (7). …”
Section: Introductionmentioning
confidence: 99%
“…27 The chemokine genes have also been included in linkage and association studies, [28][29][30][31] but despite substantial evidence for linkage and association to this chemokine cluster, data lack conclusive replication. 32 In this study, we refine the Eae18b locus to a 0.88 Mb region containing the chemokine gene cluster and show that the expression of chemokines Ccl2, Ccl11 and Ccl1 is regulated by the locus. We further present evidence for association of CCL2, CCL1 and CCL13 in a large Nordic MS material, including a possible modulatory effect from the human leukocyte antigen (HLA)-DR1*15 locus.…”
Section: Il7rmentioning
confidence: 81%
“…Genetic polymorphisms in the homologous region on human chromosome 17 have been studied for involvement in MS susceptibility, [29][30][31][32] as well as other autoimmune or chronic inflammatory diseases including RA, 60 myocardial infarction 66,67 and allergy. 68 A second cluster including chemokine genes (CCL5, CCL16, CCL14, CCL15, CCL23, CCL18, CCL3 and CCL4) located further upstream has also been studied in relation to MS, but in this study we have focused on the centromeric cluster, as this was identified in the rat linkage study.…”
Section: Discussionmentioning
confidence: 99%